2015
DOI: 10.1039/c5ta02557e
|View full text |Cite
|
Sign up to set email alerts
|

Rational design and synthesis of NixCo3−xO4 nanoparticles derived from multivariate MOF-74 for supercapacitors

Abstract: 5Mixed transition metal oxides have attracted much attention recently due to their potential application in the energy and environmental sciences. The emergency of multivariate MOFs recently attracts great research attention and provides an opportunity for multivariate mixed-metal oxides. In this work, five isostructural, single-phase MOF-74 structures with different divalent metals (MOF-74-Co, MOF-74-Ni, MOF-74-NiCo1, MOF-74-NiCo2 and MOF-74-NiCo4) were synthesised by varying the mole ratios of 10 Ni/Co mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(137 citation statements)
references
References 85 publications
5
131
0
1
Order By: Relevance
“…Owing to the homogenous dispersion of two metal ions inside the MOFs, the obtained bimetal oxides also exhibit a homogenous dispersion of two different metal ions inside the whole metal oxides, thus leading to a synergistic effect between different metal components at atomic level. For instance, Qiu and co‐workers reported the fabrication of Ni x Co 3− x O 4 by using bimetal MOF Ni‐Co‐MOF‐74 as precursor, which was employed as electrode materials for supercapacitors . By adjusting the molar ratio of Ni and Co, the authors found that Ni/Co with a molar ratio of 1:1 exhibited the highest specific capacitance (797 F g −1 at current density of 1 A g −1 ), much better than the metal oxides with only one kind of metal (119 F g −1 for NiO and 115 F g −1 for Co 3 O 4 ).…”
Section: Single Mof Derivativesmentioning
confidence: 99%
“…Owing to the homogenous dispersion of two metal ions inside the MOFs, the obtained bimetal oxides also exhibit a homogenous dispersion of two different metal ions inside the whole metal oxides, thus leading to a synergistic effect between different metal components at atomic level. For instance, Qiu and co‐workers reported the fabrication of Ni x Co 3− x O 4 by using bimetal MOF Ni‐Co‐MOF‐74 as precursor, which was employed as electrode materials for supercapacitors . By adjusting the molar ratio of Ni and Co, the authors found that Ni/Co with a molar ratio of 1:1 exhibited the highest specific capacitance (797 F g −1 at current density of 1 A g −1 ), much better than the metal oxides with only one kind of metal (119 F g −1 for NiO and 115 F g −1 for Co 3 O 4 ).…”
Section: Single Mof Derivativesmentioning
confidence: 99%
“…Subsequently, Chen group also synthesized a series of Ni x Co 3‐x O 4 , which were isomorphic to the Co 3 O 4 crystal structure derived from MOF‐74 topology phases (MOF‐74‐Co, MOF‐74‐Ni, MOF‐74‐NiCo1, MOF‐74‐NiCo2, and MOF‐74‐NiCo4, denoted Co: Ni = 1:0, 0:1, 1:1, 2:1, and 4:1) (Figure ). The relationship between metal ratios in the Ni x Co 3‐x O 4 and the electrochemical performance were explored.…”
Section: Performance Optimization Of Mof‐derived Nanostructure Metal mentioning
confidence: 99%
“…Schematic diagram of various metal oxide materials derived from multivariate MOF‐74 crystals. Ni, cyan; Co, pink; C, gray; and O, red; the H atoms are omitted for clarity [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Performance Optimization Of Mof‐derived Nanostructure Metal mentioning
confidence: 99%
“…Chen et al [79] synthesized NiCo oxides by the annealing method, in the process of which Co and Ni act as the central metal ions (Fig. 16a).…”
Section: Mofs In Combination With Other Materials As Carbon Sourcesmentioning
confidence: 99%